Direct probing of energy gaps and bandwidth in gate-tunable flat band graphene systems - Jin Jiang; Qixuan Gao; Zekang Zhou; Cheng Shen; Mario Di Luca; Emily Hajigeorgiou; Kenji Watanabe; Takashi Taniguchi; Mitali Banerjee (Nature Communications)
Abstract Moiré systems featuring flat electronic bands exhibit a vast landscape of emergent exotic quantum states, making them one of the resourceful platforms in condensed matter physics. Tuning these systems via twist angle and the electric field greatly enhances our comprehension of their strongly correlated ground states. Here, we report a technique to investigate the nuanced intricacies of band structures in dual-gated multilayer graphene systems. We utilize the Landau levels of a decoupled monolayer graphene to extract the electric field-dependent bilayer graphene charge neutrality point gap. Then, we extend this method to analyze the evolution of the band gap and the flat bandwidth in twisted mono-bilayer graphene. The band gap maximizes at the same displacement field where the flat bandwidth minimizes, concomitant with the emergence of a strongly correlated phase. Moreover, we extract integer and fractional quantum Hall gaps to further demonstrate the strength of this method. Our technique paves the way for improving the understanding of electronic band structures in versatile flat band systems.